PENGARUH KEPEMIMPINAN TRANSFORMASIONAL DAN MANAJEMEN KUALITAS TOTAL TERHADAP KINERJA KARYAWAN: PERAN PEMEDIASI KOMITMEN ORGANISASI - Purwoko Purwoko; Muhammad Ali Fikri (UNESA In Collaboration With APSMBI (Aliansi Program Studi dan Bisnis Indonesia), 2023)
The current era of business competition encourages every organization to survive by implementing various strategies. Among the various strategies, implementing total quality management and leadership can encourage organizational commitment so that employee performance increases. This study aims to determine the mediating role of organizational commitment on the effect of transformational leadership and total quality management on the performance of Micro, Small and Medium Enterprises (MSMEs) employees in the Batik sector in the Special Region of Yogyakarta. The study used purposive sampling and used questionnaires given directly to respondents. The data testing process in this study uses Smart PLS 3.0 software. The results showed that transformational leadership has a positive effect on employee performance, transformational leadership has a positive effect on organizational commitment, organizational commitment has a positive effect on employee performance, organizational commitment mediates the positive effect of transformational leadership on employee performance, total quality management has a positive effect on employee performance, organizational commitment has a positive effect on employee performance. Organizational commitment mediates the positive effect of total quality management on employee performance.